2016
DOI: 10.1016/j.jphotobiol.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel starch-based Pickering emulsions as platforms for skin photoprotection

Abstract: Green coffee oil and modified starch were recently found to have an enhanced protection effect against UV radiation. Therefore, this work aimed to develop an innovative sunscreen formulation based on Pickering emulsions concept, i.e., surfactant-free emulsions stabilized by physical UV filters associated natural oils as a key strategy for prevention against UV-induced skin damage. The Pickering emulsions of different compositions were characterized in terms of pH, mechanical, physical and microbiological stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Tan et al [252] showed that the API bioaccessibility was improved by a factor of 5 after the in vitro digestion of Even if these emulsions were intended for a food application and not for a pharmaceutical one, they all used biocompatible oil making these systems potential pharmaceutical Pickering emulsions, especially for oral administration. 45…”
Section: Biocompatible Synthetic Polymer-based Particlesmentioning
confidence: 99%
“…Tan et al [252] showed that the API bioaccessibility was improved by a factor of 5 after the in vitro digestion of Even if these emulsions were intended for a food application and not for a pharmaceutical one, they all used biocompatible oil making these systems potential pharmaceutical Pickering emulsions, especially for oral administration. 45…”
Section: Biocompatible Synthetic Polymer-based Particlesmentioning
confidence: 99%
“…Other recent work has used chitosan based Pickering emulsions as a method to enhance wound healing, where the synergistic effect of the cargo therapeutic and other components of the Pickering emulsion demonstrated improved functioning compared to the drug alone. [16] Another innovative topical application of Pickering emulsions is for sunscreens, [25,26] where the emulsifying particles can be physical UV filters in combination with an encapsulated active agent, such as melatonin. [27] Such formulations can present a stable and effective sunscreen with the added benefit of protection against oxidative stress, thanks to melatonin's free radical scavenger and antioxidant activity.…”
Section: Topical Applicationmentioning
confidence: 99%
“…Chemical UV filters are incorporated into sunscreen products to reduce skin photoaging and prevent skin cancer (Foley et al 1993;Marto et al 2016). The main chemical filters include paraaminobenzoic acid, benzophenones, cinnamates, and benzimidazole sulfonic acids.…”
Section: Chemical Sunscreens In Photoprotectionmentioning
confidence: 99%